Determinisme Teknologi dan Industri Buzzer: Pembusukan Komunikasi Politik di Media Sosial: Indonesia - Wahyudi, Dicky (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Brawijaya, 2023)
Technological determinism provides a free digital public space on social media while bringing together political opportunities that maintain buzzers. The rise in democracy has worsened with the emergence of hoaxes, fake news and hate narratives in public spaces on social media. The research aims to explain the condition of Indonesian political communication amidst technological determinism and the buzzer industry on social media. To fulfill these objectives, this research uses a qualitative approach method with literature studies, as well as Fukuyama's concepts of political order and political decay; and McLuhan's concept of technological determinism. The results of this research show that political communication is heading towards worsening conditions in the public space on social media, poor legal supremacy of the ITE Law, and a crisis of trust experienced by the government. Therefore, it is necessary to reorganize political communication on social media by improving regulations on digital public spaces, and combining political literacy with media literacy for the community. Keywords: Technological Determinism, Buzzer Industry, Public Space, Political Communication, Social Media